Pharmacist-directed vancomycin therapeutic drug monitoring in pediatric patients: a collaborative-practice model - Kashif Hussain; Rahila Ikram; Gul Ambreen; Muhammad Sohail Salat (Taylor & Francis Group, 2021)
Background Therapeutic drug monitoring (TDM) of Vancomycin (VCM) is required to prevent inappropriate dosage-associated bacterial resistance, therapeutic failure, and toxicities in pediatrics. Anecdotal experience and studies show that many healthcare institutions confront barriers while implementing TDM services, this study aimed to assess a pharmacist-directed VCM-TDM service for optimizing patient care in our institution. Materials and methods Patients aged 1 month-18 years who received intravenous VCM were included in this quasi-experimental study. The pre-implementation phase (March-June 2018) consisted of retrospective assessment of pediatric patients, the interventional phase (July 2018 to February 2020) included educational programs and the post-implementation phase (March-June 2020) evaluated the participants based on pharmacist-directed VCM-TDM services as a collaborative-practice model including clinical and inpatient pharmacists to provide 24/7 TDM services. Outcomes of the study included the mean difference in the number of optimal (i) prescribed initial VCM doses (primary) (ii) dosage adjustments and (iii) VCM-sampling time (secondary). After ethical approval, data were collected retrospectively. Results A hundred patients were there in each phase. The number of cases who were correctly prescribed initial VCM doses was significantly higher in the post-implementation phase, mean difference of 0.22, [95% CI (0.142-0.0.358), p < 0.0001]. Patients who had correct dosage adjustments in the post-implementation phase also had higher statistical significance, mean difference of 0.29, [95% CI (0.152-0.423), p < 0.05]. More correct practices of VCM-levels timing were observed in the post-implementation phase, mean difference of 0.15, [95% CI (− 0.053-0.264), p = 0.079]. Conclusion This study showed the significant role of pharmacist-directed TDM services to optimize the correct prescribing of initial VCM doses and dose adjustments.